The Effect of Principal Leadership and Work Motivation on Elementary School Teacher Performance - Wahyudi, Aris; Fitria, Happy; Rohana, Rohana (research, training and philanthropy institution Natural Aceh, 2024)
This study is driven by the necessity to comprehend how the leadership exhibited by the principal and the motivation to work may influence the performance of instructors in elementary schools. This study's primary goal was to ascertain the interrelationships between principal leadership, motivation to work, and teachers' performance in elementary schools. This research is quantitative and employs the correlation technique. This study focused on elementary school teachers located in cluster X within the city of Prabumuih. Ninety-eight individuals participated in the study. The collection of data was facilitated through the use of questionnaires and documentation, whereas the processing of data involved the application of t-tests and F-tests. According to the findings of this study, a positive relationship exists between the principal's leadership and teachers' performance in elementary schools located in cluster X, Prabumuih City. Additionally, it was found that motivation to work also positively impacted the performance of teachers in these elementary schools. As a result of this study, effective leadership demonstrated by principals and maintaining motivation to work play a significant role in enhancing teachers' performance in elementary schools. The constructive conclusions drawn from the investigation into the connection between leadership and teacher performance and the favorable impact of work motivation emphasize the potential benefits of bolstering both aspects to develop a teaching staff with enhanced productivity.